Discrimination of Men as Victims of Sexual Harassment from the Perspective of Law Number 12 Of 2022 and Gender - Imamuddin Imamuddin; Bunga Putri Ayu Nasution (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
Sexual violence is commonly associated with female victims, while cases involving male victims often receive limited attention due to social stigma, gender stereotypes, and perceptions of masculinity. This study aims to analyze discrimination against male victims of sexual violence from a gender equality perspective and examine legal protection mechanisms available under Indonesian law. The research applies a normative qualitative method through literature studies by reviewing books, journals, legal regulations, government reports, and media publications related to gender theory and sexual violence. Data validity was ensured through comparison and analysis of multiple sources. The findings indicate that male victims of sexual violence continue to experience discrimination in reporting processes, access to legal protection, and social acceptance. Gender stereotypes positioning men as strong and dominant contribute to the underreporting of cases and inadequate support systems. Although Law Number 12 of 2022 concerning Sexual Violence Crimes provides legal protection and recognizes victims’ rights to assistance, rehabilitation, and justice, implementation remains insufficiently inclusive toward male victims. Existing complaint services and legal mechanisms also tend to prioritize women and children. Therefore, strengthening gender-responsive legal frameworks, increasing public awareness, improving law enforcement sensitivity, and expanding psychological and social support systems are necessary to ensure equal protection for all victims regardless of gender. The study concludes that achieving gender equality in handling sexual violence requires inclusive legal reform and the elimination of discriminatory perceptions toward male victims to create a more equitable justice system in Indonesia.